2014
DOI: 10.1080/03602559.2014.886045
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation into the Effects of Different Nanoclays on Polyurethane Nanocomposites Properties

Abstract: Polyurethane-clay nanocomposites were prepared by in situ polymerization method. Different nanoclays were used. The morphology of nanocomposites was studied. Nanocomposites containing Cloisite 30B and Dellite 1 43B showed the exfoliation morphology. This diversity in such behaviors originated from the difference in type and amount of used modifiers. Mechanical and thermal properties were investigated. The results revealed that adding small amounts of nanoclays as modifier to polyurethane matrix led to an incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Here, the peaks at 3.29°and 4.96°related to the silicate structure and organic modifier present in the nanoclay can be highlighted (dimethylbenzylhydrogenated tallow ammonium), respectively. 53,54 In the next range (2θ between 10 and 30°), considerable intensities are observed as well. Within this region, the peaks at 20.04°and 22.04°are remarked, which are attributed to the planes 020 and −111, respectively.…”
Section: Molecular Weight Determinationmentioning
confidence: 89%
“…Here, the peaks at 3.29°and 4.96°related to the silicate structure and organic modifier present in the nanoclay can be highlighted (dimethylbenzylhydrogenated tallow ammonium), respectively. 53,54 In the next range (2θ between 10 and 30°), considerable intensities are observed as well. Within this region, the peaks at 20.04°and 22.04°are remarked, which are attributed to the planes 020 and −111, respectively.…”
Section: Molecular Weight Determinationmentioning
confidence: 89%
“…A number of studies reported the development of intercalated or exfoliated nanocomposite structures with polyolefin/montmorillonite (MMT) [ 133 , 136 142 ]. These studies revealed that the incorporation procedure into a polymer matrix is important in order to obtain complete nanoclay dispersion.…”
Section: Microporous Polymers As Carriers Of Insect Repellentmentioning
confidence: 99%
“…This synergy resulted in an increased level of compatibility between PLA and the plasticizers. Indeed, the aromatic groups present in the D43B modifier had the potential to interact with the hydroxyl groups found in both these plasticizers and PLA chains, thereby promoting improved compatibility within the blend 16,21,30,31 …”
Section: Resultsmentioning
confidence: 99%